2013
DOI: 10.1093/pcp/pct150
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone and Cytokinin Act Antagonistically in Regulating Rice Mesocotyl Elongation in Darkness

Abstract: Strigolactones (SLs) are a group of phytohormones that control plant growth and development including shoot branching. Previous studies of the phenotypes of SL-related rice (Oryza sativa) dwarf (d) mutants demonstrated that SLs inhibit mesocotyl elongation by controlling cell division. Here, we found that the expression of cytokinin (CK)-responsive type-A RESPONSE REGULATOR (RR) genes was higher in d10-1 and d14-1 mutants than in the wild type. However, CK levels in mesocotyls of the d mutants were not very di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 54 publications
2
51
0
Order By: Relevance
“…Although nothing is known about OsTCP18 of rice, OsTCP5 has been shown to be regulated by strigalactones and cytokinins and is implicated in regulating mesocotyl length37. Arabidopsis orthologs ( AtTCP5, 13 and 17 ) of these genes regulate cell proliferation and differentiation during leaf development38.…”
Section: Discussionmentioning
confidence: 99%
“…Although nothing is known about OsTCP18 of rice, OsTCP5 has been shown to be regulated by strigalactones and cytokinins and is implicated in regulating mesocotyl length37. Arabidopsis orthologs ( AtTCP5, 13 and 17 ) of these genes regulate cell proliferation and differentiation during leaf development38.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for hormone involvement in TCP-mediated growth regulation accumulated in the recent years (Nicolas and Cubas, 2016). TCP functions have been associated with abscisic acid (Tatematsu et al, 2008; González-Grandío et al, 2013; Mukhopadhyay et al, 2015), auxin (Kosugi et al, 1995; Ben-Gera and Ori, 2012; Uberti-Manassero et al, 2012; Das Gupta et al, 2014), brassinosteroid (Guo et al, 2010), cytokinin (Steiner et al, 2012; Efroni et al, 2013), GA (Yanai et al, 2011; Das Gupta et al, 2014; Davière et al, 2014), jasmonic acid (Schommer et al, 2008; Danisman et al, 2012), salicylic acid (Wang X.et al, 2015), and strigolactone signaling pathways (Dun et al, 2012; Hu et al, 2014) ( Figure 2 ).…”
Section: Tcp Functions Effect On the Cell Cycle – Direct Or Indirect?mentioning
confidence: 99%
“…Here, Gh TCP3 acts in conjunction with DECREASED APICAL DOMINANCE 2, a receptor protein that normally inactivates strigolactones in response to decreased R:FR (Drummond et al, 2015). Rice OsTCP15 is involved in the mesocotyl elongation in response to darkness and responds to strigolactone and cytokinin treatments, outlining the interplay between TCPs and different plant hormones in developmental regulation that is responsive to the environment (Hu et al, 2014). …”
Section: Mediating Environmental Signals Into Growth Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesocotyl elongation is a response to darkness, and it ceases when the tip of the coleoptile emerges into light (Robson et al 1988). In rice, Hu et al (2010Hu et al ( , 2014 have observed that the mesocotyl is highly elongated when seedlings are grown in darkness, whereas mesocotyl elongation is dramatically inhibited under light conditions. The growth of the mesocotyl is controlled by phytohormones.…”
Section: Introductionmentioning
confidence: 99%